GLANCE AT EXPLORATION ON EXISTING PRACTICES OF MOSQUE AUDIT IN MALAYSIA - Sharifah Norhafiza Syed Ibrahim; Mohd Ariff Mustafa; Kamariah Ali (Journal of Islamic, Social, Economics and Development, 2023)
Today, a mosque not only serves as a place for worship but also as a multipurpose building that may be used for other things like education center, economic hub, Muslim community center, one-stop center for travelers, and shelter for the destitute and those in need. Due to the expanding activities of a mosque, it is important for the Muslim house of worship to be properly governed and supervised by the Islamic authorities. A mosque audit is deemed necessary as a check and balance mechanism to ensure a mosque is managed within the confines of Islamic laws and regulations. This paper aims to explore current practices of Malaysian Islamic authorities in auditing mosques in Malacca and discover the obstacles and challenges in mosque audit. Data for this study were gathered using qualitative method of inquiry. A semi-structured interview was conducted with the audit personnel from the Internal Audit Department of Melaka Islamic Religious Council (MIRC). Findings of the study reveal that a mosque audit was only initiated after the MIRC received complaints from members of the public because the department lacked the resources necessary to regularly audit mosques. Since the mosque audit is still in its infancy, findings from this study are beneficial to MIRC in its efforts to establish better mosque audit mechanisms.